Ferulic Acid Ameliorates Hepatic Inflammation and Fibrotic Liver Injury by Inhibiting PTP1B Activity and Subsequent Promoting AMPK Phosphorylation - Wu, Jianzhi; Xue, Xiaoyong; Fan, Guifang; Gu, Yiqing; Zhou, Fei; Zheng, Qi; Liu, Runping; Li, Yajing; Ma, Boning; Li, Shuo; Huang, Guangrui; Ma, Lin; et al. (Frontiers in Pharmacology, 2021)
Chronic inflammation in response to persistent exogenous stimuli or damage results in liver fibrosis, which subsequently progresses into malignant liver diseases with high morbidity and mortality. Ferulic acid (FA) is a phenolic acid widely isolated from abundant plants and exhibits multiple biological activities including anti-oxidant, anti-inflammation and enhancement of immune responses. Adenosine monophosphate-activated protein kinase (AMPK) functions as a critical energy sensor and is regulated through the phosphorylation of liver kinases like LKB1 or dephosphorylation by protein tyrosine phosphatases (PTPs). However, the role of FA in carbon tetrachloride (CCl4)-induced chronic inflammation and liver fibrosis and AMPK activation has not been elucidated. Here we reported that FA ameliorated CCl4-induced inflammation and fibrotic liver damage in mice as indicated by reduced levels of serum liver function enzyme activities and decreased expression of genes and proteins associated with fibrogenesis. Additionally, FA inhibited hepatic oxidative stress, macrophage activation and HSC activation via AMPK phosphorylation in different liver cells. Mechanically, without the participation of LKB1, FA-induced anti-inflammatory and anti-fibrotic effects were abrogated by a specific AMPK inhibitor, compound C. Combining with the results of molecular docking, surface plasmon resonance and co-immunoprecipitation assays, we further demonstrated that FA directly bound to and inhibited PTP1B, an enzyme responsible for dephosphorylating key protein kinases, and eventually leading to the phosphorylation of AMPK. In summary, our results indicated that FA alleviated oxidative stress, hepatic inflammation and fibrotic response in livers through PTP1B-AMPK signaling pathways. Taken together, we provide novel insights into the potential of FA as a natural product-derived therapeutic agent for the treatment of fibrotic liver injury.